6+12x=-5+5

Simple and best practice solution for 6+12x=-5+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+12x=-5+5 equation:


Simplifying
6 + 12x = -5 + 5

Combine like terms: -5 + 5 = 0
6 + 12x = 0

Solving
6 + 12x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 12x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 12x = 0 + -6
12x = 0 + -6

Combine like terms: 0 + -6 = -6
12x = -6

Divide each side by '12'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 6(a+3)-10=-2(a+8) | | 3(x-8)=6(x+3) | | 6(a+3)-10=-2a+8 | | 10x+224-14x=188 | | X*x*7=63 | | 11=6m-1 | | W+48=-95 | | 8t^2+4t=0 | | 1-2(6-y)=y | | 10x-8=3x+3 | | 0.2z=3z | | -21b+10a=120 | | 4y+11=13 | | 3x+16-8x=19-14x+9x-3 | | 34g+17= | | X-45=108 | | 10a-21b=120 | | 700x^2+100x-16=0 | | 65-y=256 | | y=x^4-x^3+x^2-8 | | 6s-12=42s | | 6x+3y=2x+3 | | 6x+108=11-12 | | x*x+18=22 | | 4y+11=3y+4x | | (4a^2-3a+4)-(3a^2-7a+6)= | | (3a-7)+(4a+5)= | | 2(2x+3)=3(x-10) | | (2x+4)+(8x+6)=90 | | 3n-5=-48+-4n | | 5x-3x+16=x+8 | | 0.2x-0.14=0.47 |

Equations solver categories